The Association between Anthropometric Indicators and Colorectal Polyps and Diverticulosis - Najafi Mobaraki, Sahar; Joukar, Farahnaz; Maroufizadeh, Saman; Baghaee, Massood; Asgharnezhad, Mehrnaz; Mansour-Ghanaei, Fariborz (Journal of Coloproctology, 2024)
Introduction Colonic polyps and diverticulosis are common colon findings on colonoscopy. One of the risk factors of colorectal polyps and diverticulosis is the anthropometric index. Therefore, we aimed to investigate the association between the anthropometric index and colorectal findings.Methods In this cross-sectional study, we included 536 patients referred to Razi Hospital, Rasht, Iran, in 2023 for colonoscopy evaluation. Demographical data, clinical characteristics, and colonoscopy findings were recorded for further analysis. All data were analyzed using SPSS.16 by considering a significant level < 0.05Results The results showed that 35.4% of the patients had polyps, with the majority having a single polyp. The patient's mean age was 55.94 ± 13.33 years; most were females (54.1%). The most common type of polyp was pedunculated, and most were located in the sigmoid colon. The prevalence of diverticular was 11.4%, most of which were also located in the sigmoid colon. Obesity was significantly associated with an increased risk of polyps, while overweight individuals had a higher risk of diverticula (P < 0.05). Age, rural residence, and low physical activity level were identified as factors associated with an increased risk of polyps and diverticula.Conclusion The findings suggest that obesity and overweight are risk factors for polyps and diverticula, respectively. Further research is warranted to explore additional factors and develop preventive strategies for colorectal diseases. These results support the need for preventive strategies and screening programs to reduce the risk of future colorectal lesions.
Keywords: anthropometric index; body mass index; colorectal cancer; waist to hip circumstances; colonoscopy